Eosinophilic esophagitis in cystic fibrosis: A case series with long‐term follow‐up. Issue 6 (11th April 2022) - Mellor, Xochitl; Schindler, Terri; Saab, Shahrazad; Roesch, Erica; Sferra, Thomas; Sankararaman, Senthilkumar
Abstract: Challenging mealtime behaviors in young children and difficulties in meeting their dietary intake recommendations are sources of parenting stress and associated with negative quality of life. The gastrointestinal (GI) manifestations of cystic fibrosis (CF) can often present similarly to a GI pathology unrelated to CF. Specifically, this case series focuses on three toddlers with CF who presented with oral aversion and challenging mealtime behaviors and later were diagnosed with eosinophilic esophagitis (EoE). Though EoE often presents with dysphagia, younger patients commonly present with nonspecific GI symptoms such as regurgitation, emesis, abdominal pain, failure to thrive, food intolerance, and oral aversion. Given the overlap of GI manifestations in CF and EoE, it can be challenging for clinicians to diagnose the coexistent EoE in patients with CF. We describe the presenting symptoms, treatment, and successful outcomes of three pediatric patients with CF and EoE. To our knowledge, this is the second case series with a detailed description of EoE in CF.